A randomised controlled trial of the effect of hormone replacement therapy on disease activity in postmenopausal rheumatoid arthritis. Issue 2 (February 1994) - Hall, G M; Daniels, M; Huskisson, E C; Spector, T D
Abstract : OBJECTIVE--To assess the effects of hormone replacement therapy (HRT) on disease activity in postmenopausal rheumatoid arthritis (RA). METHODS--Two hundred postmenopausal outpatients (aged 45-65 years) were admitted into a single blind randomised placebo controlled trial of transdermal oestradiol (50 micrograms daily) over six months. Patients continued with routine antirheumatic medications. Compliance with HRT was monitored using serum oestradiol (E2) levels. Disease activity was monitored at entry, three and six months using erythrocyte sedimentation rate (ESR), articular index (AI), visual analogue pain scale (VPS) and early morning stiffness (EMS). RESULTS--Ninety one and 77 patients completed six months treatment with placebo and HRT respectively. There were no significant differences in baseline characteristics between the groups and no overall effects of treatment. However, 35 patients (41.6%), who completed HRT, failed to achieve serum E2 levels > 100 pmol/l at either three or six months and were considered 'poor-compliers'. In the remaining HRT 'compliers' (58.4%) there were significant improvements after six months in articular index (28.9%; p < 0.01) and pain score (21.7%; p < 0.05) compared with placebo, as well as reductions in ESR (8.9%; NS) and morning stiffness (25.2%; NS). Comparisons between HRT 'compliers' and 'poor-compliers' confirmed significant improvements in articular index (p < 0.001), pain score (p < 0.05) and morning stiffness (p < 0.001) in the 'compliers'. CONCLUSIONS--This study did not show an overall effect of HRT on disease activity when used as an adjunct therapy in postmenopausal patients. A subgroup of patients, who had greater increments in serum E2 whilst taking HRT, demonstrated improvements in some parameters of disease activity, suggesting a potential beneficial effect with good compliance and higher dose HRT. Most importantly, in the treatment of RA associated bone loss, HRT can be prescribed without fear of a disease flare up.